From Presentation to Purchase: Economic and Financial Analysis of Host ‎Characteristics in Food Live-Streaming - Zhao, Wei; He, Yue; Wang, Quanbo (International Journal of Accounting and Economics Studies, 2025)
This study examines the economic and financial implications of host characteristics in food ‎live-streaming commerce, a rapidly growing sector that has transformed digital retail. ‎Drawing on parasocial interaction theory and the stimulus-organism-response (S-O-R) framework, we investigate how streamer attributes—namely, professionalism, attractiveness, interactivity, and expertise—impact consumer trust and purchase intentions. Using secondary data from 345 consumers engaged in food live-streaming platforms, we employ structural equation modeling (SEM) and fuzzy-set qualitative comparative analysis (fsQCA) to analyze the complex relationships between host characteristics and economic outcomes. ‎Results indicate that streamer professionalism (β = 0.42, p < 0.001) and attractiveness (β = ‎‎0.38, p < 0.001) significantly enhance consumer trust, which mediates purchase intention (β = ‎‎0.51, p < 0.001). The economic analysis reveals that a one-standard-deviation increase in host ‎professionalism correlates with a 23% increase in consumer purchase value. Our findings ‎demonstrate that parasocial interaction plays a crucial mediating role (indirect effect = 0.31, p ‎‎< 0.001) between host characteristics and financial outcomes. The fsQCA results identify ‎three configurations of host attributes that lead to high purchase intentions, with ‎comprehensive trait combinations proving most effective. This research contributes to the ‎literature by integrating economic analysis with consumer psychology, providing actionable ‎insights for platform operators and content creators in the 843.93 billion global live-streaming commerce market. The study has significant implications for resource allocation, ‎streamer selection, and marketing strategy optimization in the food live-streaming sector‎.